Recovery from the Asian financial crisis: the importance of non‐monetary financial factors. (11th September 2018) - Xue, Wenjun; Taylor, Jason E.
Abstract : While it is widely accepted that monetary factors play an integral role in macroeconomic outcomes, Bernanke's (1983 ) seminal paper highlights the significant role that non‐monetary financial factors played in the downturn and recovery (or lack thereof) from the Great Depression of the 1930s in the USA. This paper explores whether Bernanke's findings can be applied to the recovery from the East Asian financial crisis of 1997–98. We show that non‐monetary financial factors played an important role in how quickly East Asian nations recovered in the years following 1998. Unlike the US experience during the Great Depression, East Asian nations generally implemented positive non‐monetary financial reforms that helped speed recovery. We find that factors correlated with a healthy banking system had a significant, positive effect upon economic growth from 1999 to 2006 and that bank system health was particularly important in those East Asian countries that had traditionally weaker banking systems. Our findings suggest that the reform of financial institutions—such as strengthening financial sector supervision and implementing prudent regulations—should be given more attention when policies are devised to help economies recover from financial crises.